Takhrij and Syarah Hadith of Agrotechnology Soil Quality in Planting - Intan Nur'aeni; Wahyudin Darmalaksana; Ahmad Soheh Mukarom; Efrin Firmansyah (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith of the Prophet Muhammad regarding agrotechnology. This research method is a qualitative type through literature study and field studies with the takhrij and syarah hadith approaches. The results and discussion of this study is to determine the quality of soil that is good for farming. The conclusion of this research is takhrij and syarah hadith of the Prophet. about soil quality with agro-technology analysis to find out how quality soil features so as to reduce failure in farming.